EXTRACTION OF HERBAL COMPONENTS – THE CASE FOR SUPERCRITICAL FLUID EXTRACTION - Andri Cahyo Kumoro; Masitah Hasan (Diponegoro University, 2008)
Malaysia is rich in heritage of sources for herbs and medicinal plants. The increasing public awareness ofthe health, environment and safety hazards associated with the use of organic solvents in herbalsprocessing and the possible solvent contamination of the final products have pointed out the need for thedevelopment of new technologies for the processing of medicinal products. This becomes the challenge forthe application of supercritical fluid extraction to enhance the economic value of Malaysian herbs.Therefore, the development of affordable, high-capacity, continuous-feed supercritical extractors inconjunction with research demonstrating its effectiveness and advantages over conventional techniquesshould be seriously taken as a consideration.